International business in a VUCA world : the changing role of states and firms - van Tulder, Rob; Verbeke, Alain; Jankowska, Barbara (Progress in international business research ;, 2019)
'IB theory and IB theorists have a long way to go to produce clarity of analysis, clear policy prescriptions and guidance for managers in a world where VUCA factors seem to be increasingly bedevilling the world of theory, managerial practice and public policy.' -Peter Buckley (in this volume). This fourteenth volume in the PIBR series is dedicated to Professor Peter Buckley, OBE, whose creative contributions to IB theory and practice over many decades are unmatched. His scientific oeuvre has continued to grow, both in depth and breadth, and reflects an evolving level of scholarly resilience that has kept pace with the increasing Volatility, Uncertainty, Complexity and Ambiguity (VUCA) characteristics of the modern environment of international business.The VUCA dimensions of the business environment that face both managers and policy makers are amplified by a wide variety of unpredictable social, economic, political and technological forces, such as: inter alia, the (post-great-recession) rise of populism; growing anti-European sentiment in the European Union; increasing protectionism; a slowdown in growth of emerging markets; the rise of the digital economy, and many more. These trends affect the competitive position of nations and firms.The present volume focuses on the threats and opportunities created by the VUCA-trends for multinational enterprises (MNEs), small and medium sized enterprises (SMEs), and international new ventures (INVs), along the following five headings:IB scholarship in a VUCA world.New Perspectives on the Interplay between Firms and the Non-Market.New Governance Challenges in International Business.New Contexts for Newly Internationalizing Firms.Contemporary Management Perspectives in IB Research.